One-Pot Synthesis and Enhanced Vis-NIR Photocatalytic Activity of NiTiO3/TiO2 Templated by Waste Tobacco Stem-Silks - Weidong Yuan; Xiaohong Chen; Yi Zhao; Ying Fang; Han Zhang; Daomei Chen; Jiaqiang Wang (Nanomaterials)
Synthesis of the photocatalysts with near-infrared light response usually involves upconversion materials or plasmon-assisted noble metals. Herein, NiTiO3/TiO2 was synthesized by using waste tobacco stem-silks as biotemplates and tetra-tert-butyl orthotitanate and nickel nitrate as precursors in a one-pot procedure. NiTiO3(1.0)/TiO2(TSS) with a mass percent of Ni 1.0% exhibited very high visible-light photocatalytic efficiency in photodegradation of tetracycline hydrochloride (TC), which is 8.0 and 2.3 times higher than TiO2 prepared without templates and TiO2(TSS) prepared without Ni, respectively. Interestingly, NiTiO3(1.5)/TiO2(TSS) even exhibited good activity under NIR light (λ = 840~850 nm) without upconversion materials or plasmon-assisted noble metals, which is 2.8 and 2.2 times than TiO2 prepared without templates and TiO2(TSS), respectively. The boosting photocatalytic activity has been shown to be attributed to efficient charge separation and transfer across a direct Z-scheme heterojunction between NiTiO3 and TiO2 and enhanced light-harvesting ability of special flaky structure reduplicated from tobacco stem-silks. This reported strategy provides a new idea for the multifunctional utilization of waste tobacco stem-silks and the synthesis of novel photocatalysts for the potential application in wastewater treatment.